The Effect of Nutritional Education and Healthy Food Processing Training Local Food Materials on Knowledge and Behavior of Mothers in Feeding for Toddlers - Sulistiawati, Febrina; Naelasari, Dian Neni (Budapest International Research and Critics University, 2021)
Nutrition education and training on healthy food processing made from local food is one of the efforts to increase knowledge and improve mother's behavior in processing healthy foods that are diverse, nutritious and balanced and safe for toddlers to consume. The purpose of this study was to determine the effect of nutrition education and training on healthy food processing made from local food on mother's knowledge and behavior in feeding toddlers. The method used in this study is a quasi-experimental with non-equivalent control group design. The sample in this study was 60 mothers of children under five who were divided into 2 groups, namely the control group and the intervention group.